Pengembangan lembar kerja siswa berbasis contextual teaching and learning untuk memfasilitasi kemampuan komunikasi matematis siswa Madrasah Tsanawiyah Darul Hikmah Pekanbaru (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
This research aimed at producing a valid and practicalstudent workbook Contextual Teaching and Learning (CTL) based that also could facilitate student mathematic communication ability on Social Arithmetic material. This research was a Research and Development (R&D) with 4-D (Define, Design, Develop, and Disseminate) model. The subjects of this research were the lecturers and teachers as validators, 5 students of VII-A3 for small group test, and 25 students of VII-B6 for large group test. Validity test questionnaire done by the experts, practicality test questionnaire and test done by students were the instruments of collecting the data. The data obtained were analyzed by using Descriptive analysis technique. This research resulted a final conclusion that validity test result of student workbook CTL based on Social Arithmetic material was stated on valid criterion with 85.21% percentage. The practicality level ofstudent workbook CTL based quality was on very practical category (87.33% of the small group and 87.47% of the large group). Whereas student mathematic communication ability after using student workbook CTL based was on high criterion 81.2%. It revealed thatstudent workbook CTL based was valid and practical, and it could facilitate student mathematic communication ability.
Keywords: student workbook; contextual teaching and learning; mathematic communication ability